Gerakan Masyarakat Hidup Sehat Pada Lansia di Posbindu Damai - Nurhayati Nurhayati; Susilawati Susilawati; Ferasinta Ferasinta; Andri Kusuma Wijaya (Universitas Pahlawan Tuanku Tambusai, 2023)
Elderly people in Indonesia have increased significantly each year so that Indonesia is included in the 5 countries that have the largest elderly population in the world. The aging process is a life cycle that is marked by a decline in the function of various organs of the body, which is characterized by the body's increasing vulnerability to disease attacks that can lead to death. This requires a special program to help prevent degenerative problems in the elderly. One effort that can be done is to change lifestyles by implementing a healthy living community movement for the elderly. The purpose of this Stimulus Community Partnership Program (PKMS) is to increase knowledge and change healthy lifestyle behaviors in an effort to increase healthy and productive older people through health education for healthy living community movements. The team conducted health education at the Posbindu Damai by coordinating with health workers at the Public Health Centre of Jalan Gedang and cadres of the Posbindu Damai, so that they could play an active role in assisting the participants' health.